Changes in Cephalometric Variables after Orthognathic Surgery and Their Relationship to Patients’ Quality of Life and Satisfaction - Tahereh Baherimoghaddam; Morteza Oshagh; Navid Naseri; Nariman Iraji Nasrbadi; Sepideh Torkan (eJournal of Oral Maxillofacial Research)
Objectives: This study was designed to assess the relationship between postsurgical cephalometric changes and quality of life and satisfaction after orthognathic surgery.